AlxGa1−xN-based semipolar deep ultraviolet light-emitting diodes. (18th May 2018) - Akaike, Ryota; Ichikawa, Shuhei; Funato, Mitsuru; Kawakami, Yoichi
Abstract: Deep ultraviolet (UV) emission from Al x Ga1− x N-based light-emitting diodes (LEDs) fabricated on semipolar ( ) ( r -plane) AlN substrates is presented. The growth conditions are optimized. A high NH3 flow rate during metalorganic vapor phase epitaxy yields atomically flat Al y Ga1− y N ( y > x ) on which Al x Ga1− x N/Al y Ga1− y N multiple quantum wells with abrupt interfaces and good periodicity are fabricated. The fabricated r -Al x Ga1− x N-based LED emits at 270 nm, which is in the germicidal wavelength range. Additionally, the emission line width is narrow, and the peak wavelength is stable against the injection current, so the semipolar LED shows promise as a UV emitter.